Protective role of Ficus deltoidea against BPA-induced impairments of the follicular development, estrous cycle, gonadotropin and sex steroid hormones level of prepubertal rats - Siti Sarah Mohamad Zaid; Shatrah Othman; Normadiah M. Kassim (BMC, 2018)
Abstract Ficus deltoidea is one of the well-known medicinal plants in Malaysia that is traditionally used by the Malay community to treat various ailments and for maintenance of female reproductive health. The objective of this study is to evaluate the potential protective roles of Ficus deltoidea against BPA-induced toxicity of the pituitary-ovarian axis in pre-pubertal female rats. In this study, four groups of pre-pubertal female Sprague Dawley rats were administered with the followings by oral gavage for a period of six weeks: NC (negative control- treated with vehicle), PC (positive control-treated with BPA at 10 mg/kg/BW), F (treated with Ficus deltoidea at 100 mg/kg/BW, then exposed to BPA at 10 mg/kg/BW) and FC (Ficus deltoidea control - treated with Ficus deltoidea at 100 mg/kg/BW). Daily vaginal smear, ovarian follicular development as well as gonadotropin and sexual-steroid hormone levels were determined. The findings showed that Ficus deltoidea demonstrated preventive role against BPA-induced toxicity on the ovaries. This was evident by the increased percentage of rats with normal estrous cycle, qualitatively reduced number of atretic follicles (as observed in histopathological examination) and normalization of the gonadotropins hormone (FSH) and sexual steroid hormone (progesterone) levels. In conclusion, Ficus deltoidea has the capability to prevent the effects of BPA toxicity in the hypothalamus-pituitary-gonadal axis of prepubertal female reproductive system, possibly due to its variety of phytochemical properties. Therefore, these findings strongly support the traditional belief that this medicinal plant is beneficial as daily dietary supplement for the maintenance of female reproductive health.